Pregnancy rates in bovines based on plasma progesterone concentration during AI under farm and village conditions - Srivastava, S K; Sanwal, P C; Umashankar, Umashankar; Varshney, V P; Sahni, K L (The Indian Journal of Animal Sciences, 2012)
Plasma progesterone was estimated in 168 cows and 130 buffaloes under village and in 356 cows and 55 buffaloes under farm conditions to find-out effects of progesterone at AI on pregancy rates in bovines. Study revealed that during AI 18.45% village and 9.26% farm cows had more than 1.0 ng/ml plasma progesterone concentration. Similarly, 22.30% village and 10.91% farm buffaloes also had progesterone concentration 1.18Â±0.10 and O.90Â±0.15 ng/ml respectively. No pregnancy was observed both in village and farm cows which had progesterone concentration more than 1.0 ng/ml at AI. However, pregnancies were observed in buffaloes inseminated with higher progesterone concentration although pregancy rate was lower in village buffaloes compared to farm buffaloes. Based on above observation, it may be concluded that more number of village animals were inseminated with higher progesterone value (> 1.0 ng/ml) compared to farm animals which resulted into no or low pregnancy. Further, it is inferred that low plasma progesterone concentration at AI is an essential criteria to achieve good pregnancy rates in bovines.